HUMAN LANGUAGE VS ANIMAL COMMUNICATION : CONSTRUCTION, INTEGRATION THEORY DESIGN FEATURE OF LANGUAGE - Samosir, Deswita Fitriani; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2024)
This study aims to compare and contrast human language with animal communication, focusing on their construction, integration, and design features based on language theories. While human language is complex, flexible, and capable of abstract thought, animal communication systems are often considered more limited, relying on instinctual signals. By examining key theoretical frameworks, including Charles Hockett's "Design Features of Language." this research analyzes both human and animal communication systems to explore their similarities and differences. A qualitative research method was used, involving a comprehensive literature review and comparative analysis of human language and animal communication examples. The findings reveal that human language has distinct features such as productivity, displacement, and recursion, which are absent in most animal communication systems. However, some animal species demonstrate rudimentary forms of syntax and symbolism. The study concludes by emphasizing the unique qualities of human language and suggesting areas for further research on the cognitive abilities of animals.